1999
DOI: 10.1021/ja992013m
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Cycloisomerization−Oxidation of Homopropargyl Alcohols. A New Access to γ-Butyrolactones

Abstract: Vinylidenemetal species, which readily form from terminal alkynes under mild conditions, have rarely been utilized as reactive intermediates in a catalytic cycle. The conversion of homopropargyl alcohols via such intermediates to metal-complexed oxacarbenes led to the development of an “oxidant” compatible with a ruthenium complex capable of performing the cycloisomerization, that would convert them to lactones. None of the oxidants known to stoichiometrically convert isolated metallooxacarbenes to esters are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(62 citation statements)
references
References 33 publications
0
60
0
2
Order By: Relevance
“…The power of this reaction was demonstrated in a concise synthesis of the fully functionalized side chain of the steroid ganoderic acid (48,Scheme 16). [31] The terminal alkyne substrate 44 was prepared by Corey-Fuchs homologation of the commercially available 3-oxopregn-4-ene-20β-carboxaldehyde (43).…”
Section: Intramolecularmentioning
confidence: 99%
See 1 more Smart Citation
“…The power of this reaction was demonstrated in a concise synthesis of the fully functionalized side chain of the steroid ganoderic acid (48,Scheme 16). [31] The terminal alkyne substrate 44 was prepared by Corey-Fuchs homologation of the commercially available 3-oxopregn-4-ene-20β-carboxaldehyde (43).…”
Section: Intramolecularmentioning
confidence: 99%
“…[48] Studies on the related reactions of bis-homopropargyl alcohols showed that employing the electron-donating ligand tris(4-methoxphenyl)phosphine gave δ-valerolactone products (Scheme 30). Interestingly, the electronics of the ligand could be tuned to give a different product.…”
Section: Intramolecularmentioning
confidence: 99%
“…(8)]. [44] This methodology was applied in a short asymmetric synthesis of (À)-muricatacin, a natural product with antitumor properties (Scheme 3). [45,46] The chemoselectivity of this oxidative cyclization of 35 for the formation of a fivepreferentially to a six-membered ring is noteworthy.…”
Section: Reviewsmentioning
confidence: 99%
“…The initial stages of the catalytic cycle are common for both pathways. Thus, vinylidene 43 is formed, and nucleophilic attack of the hydroxy group at the vinylidene carbon atom leads to the pivotal intermediate 44 …”
Section: Reviewsmentioning
confidence: 99%
“…(8)]. [44] Diese Methode fand auch Verwendung bei einer kurzen, asymmetrischen Synthese von (À)-Muricatacin, einem natür-lichen Tumortherapeutikum (Schema 3). [45,46] [48] Im vorliegenden Fall ist die Wahl einer koordinierenden Base, speziell N-Hydroxysuccinimid, entscheidend für den Umsatz, da mit anderen Basen überhaupt keine Hydropyrane erhalten wurden.…”
Section: Aufsätzeunclassified